2001
DOI: 10.1111/j.1365-2966.2001.04713.x
|View full text |Cite
|
Sign up to set email alerts
|

The magnetic field and wind confinement ofβCephei: new clues for interpreting the Be phenomenon?

Abstract: In this paper, we use the very recent spectropolarimetric observations of β Cep collected by Henrichs et al. and propose for this star a consistent model of the large‐scale magnetic field and of the associated magnetically confined wind and circumstellar environment. A re‐examination of the fundamental parameters of β Cep in the light of the Hipparcos parallax indicates that this star is most likely a 12‐M⊙ star with a radius of 7 R⊙, effective temperature of 26 000 K and age of 12 Myr, viewed with an inclinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
155
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(169 citation statements)
references
References 23 publications
13
155
1
Order By: Relevance
“…New fiberfed spectropolarimeters avoid both instrumental polarization, with the polarimeter part placed at the Cassegrain focus of the telescope, and flexures, by the use of fiber optics to feed a fixed spectrograph (Donati et al 1999). However, fibers can produce other problems depending on how they are interfaced between the two instrumental components (Eversberg et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New fiberfed spectropolarimeters avoid both instrumental polarization, with the polarimeter part placed at the Cassegrain focus of the telescope, and flexures, by the use of fiber optics to feed a fixed spectrograph (Donati et al 1999). However, fibers can produce other problems depending on how they are interfaced between the two instrumental components (Eversberg et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Several physical processes are frequently invoked to be at the origin of the structures: wind instabilities, nonradial pulsations (NRPs), and rotating global or local magnetic fields. Some recent discoveries of Zeeman signatures in early-type stars, such as b Cep (B2 III, km s ; Donati et al 2001), show that even…”
Section: Introductionmentioning
confidence: 99%
“…A field was discovered in the prototype β Cep star, β Cep = HD 205021 itself (Henrichs et al 2000;Neiner et al 2001;Donati et al 2001). The field of this star appears to be very securely detected (see Sect.…”
Section: β Cephei Pulsators and Slowly Pulsating B Starsmentioning
confidence: 99%
“…On the basis of data from the MuSiCoS spectropolarimeter, Henrichs et al (2000), Neiner et al (2001) and Donati et al (2001) have reported the detection of a weak field in HD 205021 = β Cep, a double system composed of a Be star and a pulsating star -the latter being the proto-type of β Cep pulsating stars. Schnerr et al (2006) have shown that the primary star of the β Cep system is the pulsating and magnetic star, while the Be star is a non-magnetic companion that can be separated with speckle interferometry.…”
Section: Classical Be Starsmentioning
confidence: 99%
“…This has been mainly in the context of early-type chemically peculiar (CP) stars with very strong magnetic fields (Havnes & Goertz 1984;Babel & Montmerle 1997a) but with ideas being extended recently toward applications to other hot stars and Be star phenomena (Babel & Montmerle 1997b;Donati et al 2001). Specifically, Havnes and Goertz (1984) discussed the effect of the growing '' magnetospheric '' density and mechanisms that might disrupt the field, releasing energy and producing X-rays.…”
Section: Introductionmentioning
confidence: 99%